Estudio comparativo vial entre el nuevo puente de Guayaquil Samborondón vs un corredor del sistema de tranvía de Guayaquil Samborondón. - Arcos Azuero, Darwin Fernando (2018)
One of the problems that most affects those who live in the area of Samborondón and Guayaquil, without a doubt is the vehicular congestion that is generated in various hours of the day at the height of the picot, a situation that has brought a number of drawbacks to Q Uienes try to mobilize in both directions, either towards their jobs, schools or businesses. In view of that, the objective of the research focused on the analysis of the road proposals constituted by the construction of the Guasamda bridge that would unite both populations, as well as the approach of a tram network covering the same route………